A Mediational Analysis of Occupational Stress on the Relationship Between Workplace Violence and Staff Performance: Evidence from Khyber Pakhtunkhwa Public Sector Commerce Colleges - Zaman Khan; Agustina, Tri Siwi; Faiza Mahreen (International Publisher, 2023)
This paper aims to investigate the mediating impact of occupational stress on the association of workplace violence and staff performance. This association was assessed through theoretical lenses and then verified through empirical evidence. This study is based on quantitative research using a survey instrument for data collection. Data was collected from 242 academic employees working in the public sector commerce and management sciences colleges in five big cities of Peshawar, Abbottabad, Mardan, Swat, and Noshehra in Khyber Pakhtunkhwa. This study applied Andrew F. Hayes PROCESS v3.4 to conduct mediation analysis in IBM SPSS 23. The statistical results reveal that occupational stress partially mediates the association between workplace violence and staff performance. The proposed framework sheds light on how occupational stress increases workplace violence's impact on staff performance. Thus, this study is the first of its kind to quantify the level of occupational stress in the association between workplace violence and staff performance of academic employees. The current study's findings benefit educationists, principals, administrators, and policymakers owing to educational developments.